Pseudomonas in the sinks in an intensive care unit: relation to patients. Issue 4 (April 1984) - Levin, M H; Olson, B; Nathan, C; Kabins, S A; Weinstein, R A
Abstract : Sink drains in a medical-surgical intensive care unit (ICU) were cultured during six consecutive weeks as part of a seven month prospective study of acquisition of Pseudomonas aeruginosa by ICU patients. Isolates were typed serologically and by aminoglycoside and chlorhexidine susceptibility patterns. All 11 sinks contained multiple strains of P aeruginosa; some strains persisted for weeks while others were isolated once. Of the sink isolates 56% had high level resistance to gentamicin and tobramycin whereas none of the strains found in patients. In sink isolates chlorhexidine resistance correlated with aminoglycoside resistance and with the presence of a chlorhexidine dispenser at a sink. The sequence of recovery of phenotypically similar isolates suggested that sinks were the source of at most two acquisitions of P aeruginosa by patients during the six weeks. Our study confirms that sinks may be reservoirs for large numbers of highly resistant P aeruginosa but are rarely the source of organisms colonising patients in our ICU.